2003
DOI: 10.1063/1.1629393
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of LaNi1−xCoxO3 solid solution

Abstract: We present the results of a systematic investigation of the thermal conductivity, Seebeck coefficient and electrical resistivity for selected members (x=0.3, 0.7, 0.8, and 1) of the LaNi1−xCoxO3 solid solution in the temperature range of 80⩽T⩽320 K. Substitution of Ni by Co drives the system from n-type metallic phase with low thermopower values into p-type semiconducting phase with high thermopower values of the order of hundreds of μV/K. But the thermal conductivity observed varies only slightly with the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
3
22
2
Order By: Relevance
“…[26][27][28][29][30][31][32][33] An advantage for the thermoelectric application is that the low-spin state is highly stable in Rh 3+ , which gives a large thermopower in the perovskite rhodium oxides. LaCoO 3 -based oxides show fairly good thermoelectric properties at room temperature, 34,35 but the thermopower suddenly decreases to a few μV/K above 500 K, accompanied by a spin-state crossover. [36][37][38] In contrast, LaRhO 3 -based oxides are found to exhibit a large thermopower up to 800 K, 39,40 which is theoretically explained by Usui et al 41 Comparing the transport properties between La 1−x Sr x CoO 3 and La 1−x Sr x RhO 3 , 14,[38][39][40]42 we find three differences as follows: (i) For the same doping level, the resistivity of doped LaCoO 3 is one order of magnitude smaller than that of doped LaRhO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33] An advantage for the thermoelectric application is that the low-spin state is highly stable in Rh 3+ , which gives a large thermopower in the perovskite rhodium oxides. LaCoO 3 -based oxides show fairly good thermoelectric properties at room temperature, 34,35 but the thermopower suddenly decreases to a few μV/K above 500 K, accompanied by a spin-state crossover. [36][37][38] In contrast, LaRhO 3 -based oxides are found to exhibit a large thermopower up to 800 K, 39,40 which is theoretically explained by Usui et al 41 Comparing the transport properties between La 1−x Sr x CoO 3 and La 1−x Sr x RhO 3 , 14,[38][39][40]42 we find three differences as follows: (i) For the same doping level, the resistivity of doped LaCoO 3 is one order of magnitude smaller than that of doped LaRhO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been conducted, especially on Co oxides; for instance Ca-Co-O, Bi-Sr-Co-O, Pb-Sr-Co-O, and La-Co-O were revealed to have large thermopower, S, and fairly low resistivity, q, in comparison with other oxides. [2][3][4][5][6][7][8] Koshibae et al 9 proposed that the large S comes from the orbital degeneracy of the low-spin state of Co ions.…”
Section: Introductionmentioning
confidence: 99%
“…Koshibae et al successfully revealed that the spin and orbital degeneracy of the d orbitals is important to the thermopower [9]. According to their theoretical prediction, conduction between (t 2g ) 5 and (t 2g ) 6 causes large thermopower at high temperatures in Co oxides. Rh oxides have been investigated for oxide thermoelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric materials are characterized by the dimensionless figureof-merit, ZT = S 2 T /ρκ, where S, ρ, κ and T represent thermopower, resistivity, thermal conductivity and absolute temperature, respectively. Na x CoO 2 [1] was found to be useful for high-temperature power generation, and a large number of researchers now study thermoelectric oxides [2,3,4,5,6,7,8]. In particular, the layered Co oxides with the CdI 2 -type CoO 2 block show large thermopower up to 1000 K with low resistivity [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation